A novel movement assessment for autism: The WES scale - Hynes, J.; Pineau, J.; Ramirez, M. (International Sport Coaching Journal, 2024)
Arguably the greatest responsibility of a coach is to help an athlete move better. From sports to strength and conditioning training, the athlete is constantly in motion and utilizing basic movement patterns to achieve an array of goals. With this in mind the ability of a coach to work with athletes of different autism profiles is necessary to provide a comprehensive curriculum. Of importance, the rise of autism diagnoses has dramatically increased with a 787% increase in diagnoses from 1998 to 2018. With this increase in autism diagnoses the need for coaching capacity to meet this influx is vital, with responsibility falling on coaching educators. Offering coaches continuing education to efficiently work with this population can help to promote inclusive sports and gym settings. Among these new curricula being developed, adaptive coaches have created a novel movement assessment that can be used with autistic athletes. The WES Scale movement assessment was originally created by autistic coach educator Julien Pineau. This curriculum serves to produce well-rounded coaches and gym environments where movement development can be shared with autistic athlete profiles through precise movement assessment.